Characterization and Cell Culture of a Grafted Chitosan Scaffold for Tissue Engineering - Wen-Chuan Hsieh; Jiun-Jia Liau; Yi-Jhong Li (International Journal of Polymer Science)
Poly(vinyl alcohol) (PVA) was grafted to chitosan to form a porous scaffold. The PVA-g-chitosan 3D scaffold was then observed by Fourier transform infrared spectroscopy (FT-IR). The water absorbency of PVA-g-chitosan was increased 370% by grafting. Scanning electron microscope (SEM) observations of the material revealed that the 3D scaffold is highly porous when formed using a homogenizer at 300 rpm. Compression testing demonstrated that as the amount of chitosan increases, the strength of the 3D scaffold strength reached showed that, by increasing the amount of chitosan, the strength of the 3D scaffold could be increased to 16 × 10−1 MPa. Over 35 days of enzymatic degradation, the 3D scaffold was degraded by various enzymes at rates of up to 10%. In vitro tests showed good cell proliferation and growth in the 3D scaffold.